Analysis of daily wind circulation toward sea level rise in Semarang. (June 2018) - Fitrianti, N; Haryanto, Y D; Simamora, E V S; Bintari, H F A; Hartoko, A; Anggoro, S; Zainuri, M
Abstract: Semarang is one of the coastal areas in Indonesia that frequently occur tidal flood. Tidal flood is a phenomenon where the sea water entering the land area. It can be influenced by astronomical factor that is gravity of moon and sun besides meteorological factor which also play a role in rising the sea level. Sea level rise can cause flood disaster in coastal areas if the height of coastal land is below sea level. At the time of minimum sea wave height, sea level rise is also low, so rising sea level is only played by high tidal fluctuations. Wind data used in this study. The data classified into land breeze, sea breeze and wind transition. From wind data, three classifications of wind speed are determined that is when the wind with minimum, average and maximum speeds. The method of calculating some variables of sea level rise (wave set up) as well as sea tidal observation and measurement. From this research it can be seen that sea level rise in Semarang besides caused by tidal factor is also caused by meteorological factors such as wind speed.